2011
DOI: 10.1515/iral.2011.014
|View full text |Cite
|
Sign up to set email alerts
|

More evidence concerning the Aspect Hypothesis: The acquisition of English progressive aspect by Catalan-Spanish instructed learners

Abstract: A robust finding from studies investigating the Aspect Hypothesis is that learn-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…In a very recent study carried out with 147 Catalan-Spanish learners of English as a foreign language (111 secondary school pupils and 36 university students), Muñoz and Gilabert (2011) tested the Aspect Hypothesis by means of an interview and a picture-based narrative. The findings confirmed the prototypical association between the progressive -ing marker and durative atelic predicates only in the interview task, whereas in the narrative data, the progressive was initially associated more often with accomplishment predicates than with activities.…”
Section: Formentioning
confidence: 99%
See 4 more Smart Citations
“…In a very recent study carried out with 147 Catalan-Spanish learners of English as a foreign language (111 secondary school pupils and 36 university students), Muñoz and Gilabert (2011) tested the Aspect Hypothesis by means of an interview and a picture-based narrative. The findings confirmed the prototypical association between the progressive -ing marker and durative atelic predicates only in the interview task, whereas in the narrative data, the progressive was initially associated more often with accomplishment predicates than with activities.…”
Section: Formentioning
confidence: 99%
“…Two additional factors have been found to interfere with the predictions of the Aspect Hypothesis for tutored L2 learners, namely their L1 (Collins 2002(Collins , 2004Housen 2002) and the type of task used to elicit the data (Ayoun & Salaberry 2008;Muñoz & Gilabert 2011). In her double cross-sectional study of French-speaking ESL learners in Québec, Collins (2002) found that the use of the perfect form (similar in form but not in function to the French passé composé) increased with telic predicates as an alternative to the simple past form once the latter was used productively.…”
Section: Formentioning
confidence: 99%
See 3 more Smart Citations